(3GdeQGSd GdMQHj h GdEYdGe GdYQHj (B/s - (3YHO GdZahQ,YHO GdZfj s ((3HZOGO (B:s (3eWHYI GdEQTGO ,s, 1979)
(3jSQ TYHI GdOQGSGJ GdESJQGJjLjI h GdSjGSjI HeQcR OQGSGJ GdNdjL GdYQHj Gf JbOe gPg GdOQGSI GdeeJYI ddbGQF GdYQHj(B.(3JhVjM hSjdI aYGdI aj GSJNOGe GdMQH GdfaSjI h GSGdjH GdOYGjI GdMOjKI h GgeGd GdeQGSd GdMQHj aJQGJ WhjdI ef bHd GLgRI GdGYdGe h GdOYGjI aj GdhWf GdYQHj s
Keywords: (3GdEYdGe GdYQHjs